Satisfaction With Web-Based Healthcare Content in Cancer Survivors: A Cross-Sectional Survey - Hanai, Akiko; Morino, Tappei; Shinohara, Yuki; Aoyama, Tomoki; Tsuboyama, Tadao (Frontiers in Digital Health, 2020)
Health-related web content is constantly increasing, and cancer survivors use it to manage their health and activities of daily living. However, the actual usage of and satisfaction with web contents among cancer survivors is unclear. Therefore, we conducted a web-based cross-sectional survey to understand the satisfaction with web content in those cancer survivors who use the Internet to cope with their anxiety/stress, sleeplessness, or cognitive difficulties. The survey questionnaire was e-mailed to 1.2 million voluntary registrants at a research company. Cancer survivors who accessed any content via the Internet and experienced anxiety/stress, sleeplessness, or cognitive difficulties were included in the study. Out of the 412 survivors who completed the survey, 357 experienced some degree of anxiety or stress, 258 experienced sleeplessness, and 161 experienced some cognitive difficulties, such as forgetfulness or lack of attention. They used web contents to record their health or (n = 205), relieve their anxiety or stress (n = 238), and devise activities of daily living (n = 232) during cancer therapy, including surgery, chemotherapy, and radiation. The web contents included “interactive contents” (users engage with the web content by responding to it in some form), “non-interactive contents” (information medium without any user engagement), “web-storage,” or “scrolling.” Multivariate logistic regression revealed greater satisfaction with “interactive contents” in cancer survivors. This reflects that the sharing of personal experiences as well as objective information should be considered to create satisfying and effective web contents.